2019
DOI: 10.1016/j.jsps.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient counselling on the common cold treatment at Slovak community pharmacies using mystery shopping

Abstract: BackgroundUp to now, there have been no data on patient counselling in the Slovak community pharmacies. The literature provides a wide range of activities for which mystery shopping methodology be used, including assessment of patient counselling.Aims and objectivesTo assess patient counselling on the common cold treatment with OTC medicine containing zinc provided by Slovak community pharmacists. To analyse this counselling considering the set scenarios, counsellors and their age.Methods54 pharmacy students v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
0
23
1
Order By: Relevance
“…As it has been confirmed over decades, community pharmacists are the first and most common health-care professionals approached by patients seeking medical advice, including advice about acute or chronic conditions. [ 14 17 21 ] Hence, pharmacists’ skills are highly sought after to provide this important community service. [ 21 22 ] The results of this study highlight the overall poor skills of pharmacists in asking questions for differential diagnosis between the two conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been confirmed over decades, community pharmacists are the first and most common health-care professionals approached by patients seeking medical advice, including advice about acute or chronic conditions. [ 14 17 21 ] Hence, pharmacists’ skills are highly sought after to provide this important community service. [ 21 22 ] The results of this study highlight the overall poor skills of pharmacists in asking questions for differential diagnosis between the two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Community pharmacists play a vital role in the differentiation, assessment, and treatment of such conditions. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies show that this kind of information significantly increases adherence, improves treatment outcomes, and accelerates the achievement of target treatment effects. [24][25][26] Polish pharmacists should pay more attention to patients and their ailments, as well as to informing them of the effects of a given medication. This information is extremely important for the safety of pharmacotherapy and can contribute to an increased adherence.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 Internationally, the provision of pharmaceutical consultations for patients with cough in community pharmacies is suboptimal, including Indonesia. [20][21][22] There are deficiencies in many aspects of pharmaceutical counselling for cough, including lack of history taking and inappropriate advice provision. [20][21][22] In developing countries, studies have identified several factors contributing to these deficiencies.…”
Section: 6mentioning
confidence: 99%
“…[20][21][22] There are deficiencies in many aspects of pharmaceutical counselling for cough, including lack of history taking and inappropriate advice provision. [20][21][22] In developing countries, studies have identified several factors contributing to these deficiencies. [23][24][25] In Indonesia, previous research has identified three main factors influencing pharmaceutical consultation performance: pharmacy staff-patient interaction, the organisational context of the pharmacy, and the external pharmacy environment (Figure 1).…”
Section: 6mentioning
confidence: 99%